Solo disponible en BuenasTareas
• Páginas : 3 (697 palabras )
• Descarga(s) : 0
• Publicado : 10 de septiembre de 2010

Vista previa del texto
DESPEJAR INCOGNITA.
1.- 3x + 2 = 0
3x = -2
x = -2 / 3
2.- 4 – 2x = 0
4 = 2x
4 / 2 = x
x = 2
3.- x / 3 + 4 = x - 3 / 2
x / 3 - x = -4 - 3 / 2
x / 3 - 3x / 3 = -8 / 2- 3 / 2
-2x / 3 = -11 / 2
2 (-2x) = 3 (-11)
-4x = -33
x = -33 / -4
x = 8.25
4.- 5x – 4 = 2 - x / 2
5x + x / 2 = 2 + 4
10x / 2 + x / 2 = 6
11x / 2 = 6
11x = 2 (6)11x = 12
x = 12 / 11
x = 1. 0909
5.- 100 = 80 (1 + 1.5n)
100 / 80 = 1 + 1.5n
1.25 = 1 + 1.5n
1.25 – 1 = 1.5n
0.25 = 1.5n
0.25 / 1.5 = n
n = 1.6667
6.- 11 – 0.3x = 0.83- 0.3x = 0.83 – 11
-0.3x = -10.17
x = -10.17 / -0.3
x = 33.9
7.- 300 = 17.2 (x - 2)
300 / 17.2 = (x – 2)
17.4418 = x – 2
17.4418 + 2 = x
x = 19.4418
8.- y / 5 + 2y – y/ 3 = 2
(3y + 30y – 5y) = 2
28y = 2
y = 2 / 28
y = 0.0714
9.- 75.3 = 42.8 (1 + 29)
????
10.- (1 / 4) (x – 3) = 5 – x
x(1 / 4) – 3(1 / 4) = 5 – x
x / 4 – 3 / 4 = 5 – x
x /4 + x = 5 + 3 / 4
x / 4 + 4x / 4 = 20 / 4 + 3 / 4
5x / 4 = 23 / 4
5x = (4 / 4) 23
5x = 23
x = 23 / 5
x = 4.6
11.- 3 / x + 2 / 3 = 2
3 / x = 2 – 2 / 3
3 / x = 6/ 3 – 2 / 3
3 / x = 4 / 3
3 (3) = 4 (x)
9 = 4x
9 / 4 = x
x = 2.25
12.- 3 / (x – 2) = 4 – 1 / 3
3 = (x – 2) (4 – 1 / 3)
3 = [ (x – 2) (4) ] – [ (x – 2) (1 / 3) ]
3= [ (4x – 8) ] – [ (x/3 – 2/3) ]
3 = 4x -8 - x/3 + 2/3
3 = 4x - x/3 -8 + 2/3
3 = 12x/3 – x/3 -24/3 + 2/3
3 = 11x/3 - 22/3
3 + 22 / 3 = 11x / 3
9 / 3 + 22 / 3 =11x / 3
31 / 3 = 11x / 3
31 = 11x
31 / 11 = x
x = 2.8181
13.- x + 3 = 2.8
x = 2.8 – 3
x = - 0.2
14.- 2 – x = 42.5
- x = 42.5 + 2
x = - 44.5
15.- (1 + i / 4)4= 22.5
1 + i / 4 = 4 22.5
1 + i / 4 = 2.1779
i / 4 = 2.1779 – 1
i / 4 = 1.1779
i = 1.1779 (4)
i = 4.7117
16.- (1 + x / 3)8 = 1.276
1 + x / 3 = 8 1.276
1 + x / 3 =...